2017
DOI: 10.3906/vet-1610-82
|View full text |Cite
|
Sign up to set email alerts
|

Morphological abnormalities of blood and bone marrow leukocytes and age-related changes in different leukocyte counts in the American mink (Neovison vison)

Abstract: The sapphire mink is a unique animal model to study cellular morphology. It demonstrates abnormal leukocytes like in patients with Chédiak-Higashi syndrome. We aimed to determine the morphologic features of blood and bone marrow leukocytes in the sapphire mink and dark-brown mink (wild type). In addition, were assessed age-related changes in total white blood cell (WBC) and differential WBC counts. We conclude that the sapphire mink has a morphological leukocyte defect (abnormal granules). We observed that abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is speculated that increased susceptibility in some genotypes (fur color type) of mink to infections may be one of the explanation for variation in mortality between farms. In a previous study, we found that sapphire puppies showed a delay in immune and hematopoietic system development compared to standard (brown wild type) puppies [13]. In addition, sapphire mink with Aleutian coat color allele are characterized by abnormal morphology and dysfunction of leukocytes.…”
Section: Highlightsmentioning
confidence: 87%
“…It is speculated that increased susceptibility in some genotypes (fur color type) of mink to infections may be one of the explanation for variation in mortality between farms. In a previous study, we found that sapphire puppies showed a delay in immune and hematopoietic system development compared to standard (brown wild type) puppies [13]. In addition, sapphire mink with Aleutian coat color allele are characterized by abnormal morphology and dysfunction of leukocytes.…”
Section: Highlightsmentioning
confidence: 87%